Про результати використання квадрокоптера для обліку кількісних характеристик любительського рибальства на Дніпровському водосховищі в зимовий період - Новіцький, Роман Олександрович; Novitsky, R. A.; Novitsky, R. O.; Novitskiy, R. A.; Novitskiy, R. O.; Novickii, R. A.; Novitskij, R. A.; Novitskij, R. O.; Nowicki, R. A.; Novickij, R. A.; Novitskyy, R. O.; Novitskyi, R. O.; et al. (Харківський нац. ун-т ім. В. Н. Каразіна, 2021)
За результатами проведених досліджень, анкетування та опитування рибалок-любителів і місцевих мешканців, визначена нагальна необхідність в організації постійних природоохоронних рейдів на акваторії верхньої ділянки Дніпровського водосховища взимку. In the winter of 2018–2019, 2020–2021, a quadrocopter was used to determine the quantitative and qualitative indicators of amateur fishing in the Dniprovske reservoir. We observed the water area of the upper and lower parts of the Dniprovske reservoir with a total area of 2530 hectares. Data were obtained on the daily attendance of the water area of the right bank of the water reserve on the upper section by 620 amateur fishermen. In winter, within the boundaries of the city of Dnipro, there are 184+7 fishermen per hectare of water area. Among the amateurs there are those who violate the rules of fishing. It is proposed to carry out permanent environmental raids in winter on the upper section of the Dniprovske reservoir.
About the results of using the quadrocopter to take into account the quantitative characteristics of amateur fishing in the Dniprovske Reservoir in winter
Новіцький Роман Олександрович https://orcid.org/0000-0001-9373-5759
Keywords: любительське рибальство; liubytelske rybalstvo; зимове рибальство; zymove rybalstvo; Дніпровське водосховище; Dniprovske vodoskhovyshche; рибалки-любителі; rybalky-liubyteli; БПЛА; BPLA